Systematic Review of the Diagnostic Validity of Brief Cognitive Screenings for Early Dementia Detection in Spanish-Speaking Adults in Latin America - Custodio, Nilton; Duque, Lissette; Montesinos, Rosa; Alva-Diaz, Carlos; Mellado, Martin; Slachevsky, Andrea (Frontiers in Aging Neuroscience, 2020)
Objectives: To evaluate the validity of brief cognitive screening tools (BCS) designed to diagnosis mild cognitive impairment (MCI) or dementia in Spanish-speaking individuals from Latino -America over the age of 50 years. Methods: Systematic search of titles and abstracts of Medline, Biomed Central, Embase, Scopus, Scirus, PsycInFO, LILACS, and Scielo was conducted. Only papers written in English and Spanish involving samples from Spanish-speaking Latin-American and published until 2018 were considered. Standard procedures were applied for reviewing the literature. The data related to the study sample, the methodology and procedures applied, as well as the performance obtained with the corresponding BCS were captured and systematized. Results: Eleven of 211 articles met the inclusion criteria. The studies involved mainly memory clinics-based samples, with the exception of two studies from an adult day care centers, one from a primary care clinic and one from a community-based sample. All the studies originate of five countries from 20 countries of LA. All the studies used standardized diagnostic criteria for the diagnosis of dementia and MCI, nevertheless the diagnostic protocols applied differed. Most studies reported samples with an average of 10 years of education and only one reported a sample with an average of fewer than 5 years of education. No publications to date have included an illiterate population. MoCA is the most widely-used BCS in LA, but this has significant impact of education level Conclusions: Existing evidence is limited. However, the findings in LA populations suggest the MoCA requires cultural adaptations and different cut-off points according to education level and the diagnostic validity of the IFS should be evaluated in populations with a low education level. Considering the heterogenous education, more study spatially in illiterate and indigenous population are needed.